Hubungan Tingkat Kecemasan Dengan Peningkatan Tekanan Darah pada Pasien Pre Fiber Optik Bronchoscopy (FOB) di RSP DR. ARIO WIRAWAN SALATIGA - Rahayu Winarti; Fitrianingsih Fitrianingsih (Jurnal Kesehatan Amanah, 2024)
Background: FOB supporting survey is an interrogation option to establish the diagnosis and as a therapeutic in pulmonology medicine. Excessive anxiety and increased blood pressure became one of the obstacles to his examination. The study aims to determine the relationship between anxiety levels and increased blood pressure of Pre-Fiber Optic Bronchoscopy patients at RSP dr. Ario Wirawan Salatiga City. Method: This research is Correlative Descriptive Research using quantitative methods with a cross-sectional approach and observational approach to 32 respondents. This research used Non Probalility Sampling Technique with Consecutive sampling approach. The research instrument used Hamiltons Anxiety Rating Scale (HARS). Bivariate analysis of the Spearman Rank correlation test used in this research. Results: The majority of respondents had anxiety as much as 17 (53.1%). Increased blood pressure occurred in 18 respondents (56.25%). The results of the Spearman p value rank correlation test is 0.000 with a correlation of 0.953 mean that there is a very strong correlation with the direction of a positive relationship between anxiety levels and increased blood pressure of pre-FOB patients at IBS RSPAW Salatiga. Conclusion: There is a significant relationship between Anxiety Levels and Increased Blood Pressure of pre-FOB patients at IBS RSPAW Salatiga so that the higher the level of anxiety, the increase in blood pressure will occur.